Unlocking Reading Potential: Does English Comics Webtoon Impact Students’ Narrative Text Comprehension? - Larisa, Intan; Erlidawati, Erlidawati; Rahman, Fadhlur (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2023)
The purpose of this study aimed to examine the effectiveness of English comic webtoons as an instructional tool for improving reading comprehension abilities to traditional teaching methods. The study used a quasi-experimental design and a simple random sampling technique to select participants. The study included two classes: Class X-MIPA 2 was designated as the experimental group, and Class X-MIPA 1 was designated as the control group. The research involved 52 students in total. Pre- and post-tests were used to collect data, which was then statistically analyzed using the t-test procedure. The study's findings revealed a statistically significant difference in academic performance between the experimental and control groups. There was a significant improvement in the students' reading comprehension scores after the treatment was completed. The computed test statistic (t-test) was 6.44, which was greater than the critical value of 1.68. This study's findings led to the acceptance of the research hypothesis (Ha) and the rejection of the null hypothesis (Ho). The effectiveness of using English comic webtoons as an instructional medium for improving the reading comprehension skills of tenth-grade students at MAS Ulumuddin, specifically in relation to narrative texts, is highlighted in this study. This study provides important insights for teachers looking for visually appealing methods to improve reading comprehension in the classroom.The study employed a quasi-experimental design and utilized a simple random sampling technique for participant selection. reading comprehension in the classroom.